Comparative Proteomics of Human Milk From Eight Cities in China During Six Months of Lactation in the Chinese Human Milk Project Study - Sari, Ratna Nurmalita; Pan, Jiancun; Zhang, Wenyuan; Li, Yuanyuan; Zhu, Huiquan; Pang, Xiaoyang; Zhang, Shuwen; Jiang, Shilong; Lu, Jing; Lv, Jiaping (Frontiers in Nutrition, 2021)
Human milk is the golden standard of infant nutrition that can protect immature body function and enhance nutrition metabolism to ensure infant growth. Region specificity and lactation period could change the protein composition in human milk. In this research, proteomics analysis was used to compare proteomes across 8 cities which represented northeast, northwest, southeast, southwest, east, north and central regions of China, including Harbin, Lanzhou, Guangzhou, Chengdu, Jinhua, Weihai, Zhengzhou and Beijing. Proteins varied significantly among cities. These different proteins were mainly involved in the process of platelet degranulation, innate immune response and triglyceride metabolic process, which might be due to different living environments. These differences also lead to variation in protection and fat metabolism from mothers to infants in different cities. Four proteins expressed differently during 6 months of lactation, including Dipeptidyl peptidase 1, Lysozyme C, Carbonic anhydrase 6, and Chordin-like protein 2. The change of these proteins might be because of the change of growth needed for infants. The findings in our results might help improve the understanding of human milk as well as designing infant formula.